Acceptability of an open-label wait-listed trial design: Experiences from the PROUD PrEP study. - Mitzy Gafos; Elizabeth Brodnicki; Monica Desai; Sheena McCormack; Will Nutland; Sonali Wayal; Ellen White; Gemma Wood; Tristan Barber; Gill Bell; Amanda Clarke; David Dolling; et al. (PLoS ONE)
Background PROUD participants were randomly assigned to receive pre-exposure prophylaxis (PrEP) immediately or after a deferred period of one-year. We report on the acceptability of this open-label wait-listed trial design. Methods Participants completed an acceptability questionnaire, which included categorical study acceptability data and free-text data on most and least liked aspects of the study. We also conducted in-depth interviews (IDI) with a purposely selected sub-sample of participants. Results Acceptability questionnaires were completed by 76% (415/544) of participants. After controlling for age, immediate-group participants were almost twice as likely as deferred-group participants to complete the questionnaire (AOR:1.86;95%CI:1.24,2.81). In quantitative data, the majority of participants in both groups found the wait-listed design acceptable when measured by satisfaction of joining the study, intention to remain in the study, and interest in joining a subsequent study. However, three-quarters thought that the chance of being in the deferred-group might put other volunteers off joining the study. In free-text responses, data collection tools were the most frequently reported least liked aspect of the study. A fifth of deferred participants reported 'being deferred' as the thing they least liked about the study. However, more deferred participants disliked the data collection tools than the fact that they had to wait a year to access PrEP. Participants in the IDIs had a good understanding of the rationale for the open-label wait-listed study design. Most accepted the design but acknowledged they were, or would have been, disappointed to be randomised to the deferred group. Five of the 25 participants interviewed reported some objection to the wait-listed design. Conclusion The quantitative and qualitative findings suggest that in an environment where PrEP was not available, the rationale for the wait-listed trial design was well understood and generally acceptable to most participants in this study.